Effect of Islamic Work Ethics on Dimensions of Organizational Justice: A Case of Banks of District Peshawar, KP-Pakistan - MAAZ UD DIN; DR.FAISAL KHAN; DR. MUHAMMAD FAIZAN MALIK (Journal of Business & Tourism, 2021)
The attention of business ethics from Islamic viewpoint has become more significant for business in this modern era. The aim of this study is to examine the consequence of Islamic work ethics on justice perception among the banks of District Peshawar. The concept of organizational justice integrated three measurements, specifically procedural, interactional and distributive justice. Practicing and Potential Personnel were surveyed and adopted questionnaire was used for data collection tools. The sample was collected from 205 employees from different banks operating in District Peshawar. The result proposed that Islamic work ethics significantly contribute the three levels of fairness perceptions. Furthermore, Islamic work ethics influence dimensions of organizational justice positively. Limitations, implications and suggestions for future work are also discussed in this study.